Patterns of Dietary Fluoride Supplement Use in Children from Birth to 96 Months of Age - Abed Al-Hadi Hamasha, BDS, MS; Steven M. Levy, DDS, MPH; Barbara Broffitt, MS, John J. Warren, DDS, (Blackwell Synergy, 2005)
This paper reports on fluoride supplement use from birth to age 96 months.